Cancer-Associated Thrombosis: Not All Low-Molecular-Weight Heparins Are the Same, Focus on Tinzaparin, A Narrative Review. (19th July 2022) - Fioretti, Agnese Maria; Leopizzi, Tiziana; Puzzovivo, Agata; Giotta, Francesco; Lorusso, Vito; Luzzi, Giovanni; Oliva, Stefano
Abstract : Cancer-associated thrombosis (CAT) is the second main cause of cancer death with high related mortality and morbidity, leading to anticancer agent delays and interruptions. The recommended therapy, low-molecular-weight heparin (LMWH), however, is burdensome for patients and costly for society, as treatment should last until cancer is no longer active, even indefinitely. Tinzaparin is a manageable, efficient, safe, and cost-effective option. Compared to the other LMWHs, advantages are single-daily dose and safety in the elderly and those with renal impairment (RI). The purpose of this review is to critically discuss recent data on its efficacy and safety in CAT.